2015
DOI: 10.1152/ajpheart.00503.2014
|View full text |Cite
|
Sign up to set email alerts
|

Akt/eNOS signaling pathway mediates inhibition of endothelial progenitor cells by palmitate-induced ceramide

Abstract: Palmitate (PA) impairs endothelial progenitor cells (EPCs). However, the molecular mechanism underlying the suppressive function of PA remains largely unknown. Ceramide, a free fatty acid metabolite, mediates multiple cellular signals. We hypothesized that ceramide acts as an intermediate molecule to mediate inhibition of EPCs by PA. We first demonstrated that PA could inhibit the attachment, migration, and tube formation of EPCs through suppression of the Akt/endothelial nitric oxide (NO) synthase (eNOS) sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…eNOS has been suggested to play a key role in the bioactivation of early endothelial progenitor cells [12]. In our previous study, we also demonstrated that the eNOS inhibitor significantly decreased the infiltration of endothelial progenitor cells in transplanted lung tissue by interfering with eNOS expression [14].…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…eNOS has been suggested to play a key role in the bioactivation of early endothelial progenitor cells [12]. In our previous study, we also demonstrated that the eNOS inhibitor significantly decreased the infiltration of endothelial progenitor cells in transplanted lung tissue by interfering with eNOS expression [14].…”
Section: Discussionmentioning
confidence: 59%
“…Previous studies have shown that NO produced by eNOS controls vascular remodelling and angiogenesis. The AKT/eNOS pathway has been suggested to play a pivotal role in bioactivation of endothelial progenitor cells, such as their mobilization, differentiation, homing and angiogenic properties [12,13]. Moreover, in our previous study, we found that eNOS inhibitor (L-NIO) decreases the recruitment of endothelial progenitor cells in transplanted lung [14].…”
Section: Introductionmentioning
confidence: 77%
“…In this study, we established a rat CPB model to observe the effect of ECFCs on CPB-related lung injury. Moreover, the eNOS plays a pivotal role in bioactivation of early endothelial progenitor cells [12], and we also found that eNOS inhibitor (L-NIO) decreased the recruitment of endothelial progenitor cells in transplanted lung [13]. We postulated that eNOS also plays a pivotal role in the bioactivation of ECFCs.…”
Section: Introductionmentioning
confidence: 54%
“…After CPB, apoptosis also played a pivotal role in lung injury [42]. Both inflammatory factors (TNF-α) and reactive oxygen species induced by lung ischaemia lead to cell apoptosis [43] eNOS has been suggested to play a key role in the bioactivation of early endothelial progenitor cells [12]. In our previous study, we also demonstrated that the eNOS inhibitor significantly decreased the infiltration of endothelial progenitor cells in transplanted lung tissue by interfering with eNOS expression [13].…”
Section: Discussionmentioning
confidence: 86%
“…Ceramide accumulation inhibits EPCs proliferation, migration, and tube formation via its inhibition of Akt/eNOS pathway [151].…”
Section: Ceramide and Sphingolipidsmentioning
confidence: 99%